Experimental Evidence of the Long-Term Survival of Infective African Swine Fever Virus Strain Ba71V in Soil under Different Conditions - Prodelalova, Jana; Kavanova, Lenka; Salat, Jiri; Moutelikova, Romana; Kobzova, Sarka; Krasna, Magdalena; Vasickova, Petra; Simek, Bronislav; Vaclavek, Petr (Pathogens (Basel, Switzerland), 2022)
The survival of African swine fever virus (ASFV) on different matrices and its infectivity in wild as well as domestic swine is still a matter of interest. ASFV is resistant to environmental effects; this fact is enhanced by the presence of organic material. Therefore, the aim of this work was to determine the ability of laboratory ASFV to survive in soil at different temperatures (4 and 22 °C) and with and without the presence of blood using culture procedures. The suitability of the procedure for determining the viability and titre of the ASFV field strain by the hemadsorption method was also verified, when a higher decrease in virus infectivity in the case of clay compared with peat was demonstrated. The stability of the virus was clearly temperature-dependent, the infectious virus was detected after 112 days, and the viral DNA was still detected in the matrix 210 days after inoculation in a relatively high and stable concentration (between 106 and 107 genome equivalents/mL). Based on this knowledge, soil and other environmental samples could provide rapid and reliable information on the disease outbreak and serve as indicators of the risk posed by the affected locality.
Keywords: hemadsorption; ASFV; stability; field isolates; infectivity testing